2011
DOI: 10.1002/hyp.8077
|View full text |Cite
|
Sign up to set email alerts
|

Flood frequency analysis of Turkey using L-moments method

Abstract: Abstract:The index flood procedure coupled with the L-moments method is applied to the annual flood peaks data taken at all streamgauging stations in Turkey having at least 15-year-long records. First, screening of the data is done based on the discordancy measure (D i ) in terms of the L-moments. Homogeneity of the total geographical area of Turkey is tested using the L-moments based heterogeneity measure, H, computed on 500 simulations generated using the four parameter Kappa distribution. The Lmoments analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 33 publications
0
35
0
9
Order By: Relevance
“…The good applicability of the GEV model, which has shape (к), scale (α) and position (β) parameters, was also observed by Seckin, Haktanir and Yurtal (2011) as to the analysis of maximum stream flows in Turkey, where the model was the best adjusted to 498 of the 543 gauging stations considered. Malekinezhad, Nachtnebel and Klik (2011), comparing five 3-parameter PDFs, found that the GEV model was the only suitable for all the 3 homogeneous regions identified in the Namak-Lake basin, central Iran.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…The good applicability of the GEV model, which has shape (к), scale (α) and position (β) parameters, was also observed by Seckin, Haktanir and Yurtal (2011) as to the analysis of maximum stream flows in Turkey, where the model was the best adjusted to 498 of the 543 gauging stations considered. Malekinezhad, Nachtnebel and Klik (2011), comparing five 3-parameter PDFs, found that the GEV model was the only suitable for all the 3 homogeneous regions identified in the Namak-Lake basin, central Iran.…”
Section: Resultsmentioning
confidence: 77%
“…GEV and Kappa. The improved estimate of maximum hydrological variables resulting from the application of multiparameter PDFs, compared to traditional two-parameter ones, i.e., Normal, LN-2P, Gumbel and Gamma, is widely demonstrated in studies conducted in various regions of the world (EATON; CHURCH; HAM, 2002;KJELDSEN;SMITHERS;SCHULZE, 2002;KUMAR et al, 2003;CHATTERJEE, 2005;NOTO;LA LOGGIA, 2009;SECKIN;HAKTANIR;YURTAL, 2011;BESKOW et al, 2015). The evaluation of traditional and multiparameter PDFs for the adjustment of annual maximum stream flow series as performed in this study, corroborates the findings of Beskow et al (2015), who reported on the importance of the analysis of various theoretical PDFs, from the simplest to those with multiparameters, in order to obtain that which best represents the frequency distribution of the sample.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[14], Naghavi ve Yu [15], Şorman [16], Seckin [17] Seckin vd. [18] Seckin vd. [19], Saf [20], Dodangeh vd.…”
Section: Gi̇ri̇ş (Introduction)mentioning
confidence: 99%